A Cultural Acculturation: The Code-Mixing and Language Meaning in ‘Geef Mij Maar Nasi Goreng’ Song - Sari, Fransiska Marta; Sri Utami; Nensy Megawati Simanjuntak (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research explores the phrase